A Grade-Level Comparative Study of English Communication Anxiety and English Oral Skills Self-Efficacy of English Program Grades 7 to 9 Students at the Demonstration School of Ramkhamhaeng University - Rerkjaraskul, Chakrit; Lynch, Richard (Scholar: Human Sciences, 2021)
This study investigated students’ perception of English communication anxiety and of English oral skills self-efficacy, and subsequently conducted a grade-level comparison in terms of these variables. The sample of this study consisted of 66 English Program Grades 7 to 9 students at The Demonstration School of Ramkhamhaeng University in the academic year 2018 - 2019. The study employed a quantitative research methodology utilizing two questionnaires to collect data. The first questionnaire focused on issues relevant to anxiety, shyness, and physical reactions towards speaking in an English language classroom. The second questionnaire asked students to make judgments about their capabilities to accomplish specific tasks using English in listening and speaking contexts. The quantitative data was analyzed by using descriptive statistics – means and standard deviations, while statistical hypotheses were tested by One-way Analysis of Variance (ANOVA). There were four main findings. First, the respondents had an overall moderate level of English communication anxiety. Second, the respondents had an overall high level of English oral skills self-efficacy. Third, there was not a significant grade-level difference in English communication anxiety. Finally, there was not a significant grade-level difference in English oral skills self-efficacy. The study concludes with recommendations for practice and for future research.